Vertical and Radial Distribution of Atomic Carbon in Hd 163296 - Miley, J (EDP Sciences, 2024)
Context. In protoplanetary disks, atomic carbon is expected to originate from the photo dissociation region at the disk surface where CO is dissociated by ultraviolet (UV) photons coming from the stellar, or external interstellar, radiation field. Even though atomic carbon has been detected in several protoplanetary disks, there is a lack of spatially resolved observations of it. Aims. For the HD 163296 protoplanetary disk, we aim to obtain both the radial and vertical structure of [CI] = 3P1-3P0 line emission and perform the first direct comparison of this tracer with the optically thick line emission 12CO J = 2-1. Methods. We used archival ALMA data for [CI] = 3P1-3P0 and previously published12 CO J = 2-1 data in HD 163296. Through the disksurf software, we extracted the vertical structure; meanwhile, we obtained the radial profiles directly from imaging. Brand new DALI modeling was employed to perform a direct comparison with the data. Results. We find that these tracers are colocated radially but not vertically, where the 12CO J = 2-1 emission is, on average, located at higher altitudes, as is also the case for other tracers in the same disk. Conclusions. Due to this difference in the vertical height of the emission, the optically thick 12CO J = 2-1 emission line appears to trace the highest altitudes, despite the expected formation mechanism of [CI] in the disk. The latter phenomena may be due to efficient mixing of the upper layers of the disk, or UV photons penetrating deeper than we expected. © 2022 S. Karger AG, Basel.